Phenolic Fractions from Dandelion Leaves and Petals as Modulators of the Antioxidant Status and Lipid Profile in an In Vivo Study - Michał Majewski; Bernadetta Lis; Jerzy Juśkiewicz; Katarzyna Ognik; Małgorzata Borkowska-Sztachańska; Dariusz Jedrejek; Anna Stochmal; Beata Olas (Antioxidants, 2020)
Alcoholic leaf and petal fractions of Taraxacum officinale (dandelion) were previously demonstrated to exert in vitro antioxidant and antithrombotic activities in blood plasma and platelets. Eight-week-old male Wistar rats (n = 6) were supplemented for four weeks with dandelion fractions (694 mg/kg of diet = 11.9 ± 0.6 mg daily). Dandelion leaf and petal fractions, which delivered daily 4.10 ± 0.05 and 1.41 ± 0.07 mg l-chicoric acid, respectively, were shown to exert antioxidative actions, measured as decreased levels of thiobarbituric acid-reactive substances (TBARS) in the spleen (≈0.8-fold, leaves and petals), brain (0.53-fold, leaves) and thoracic arteries (0.59-fold, petals). Moreover, petal fraction increased thiols in the blood plasma (1.58-fold), while leaf fraction decreased protein carbonylation levels (0.59-fold). Additionally, dandelion leaf fractions modified the lipid profile: decreased triglyceride (0.44-fold), total cholesterol (0.73-fold), lipoprotein combine index (0.32-fold) and the atherogenic index of plasma (0.62-fold). Dandelion fractions showed a beneficial decrease effect in the participation of cyclooxygenase products in the noradrenaline-induced vascular contractions of thoracic arteries. Meanwhile, only the dandelion leaf fraction augmented acetylcholine-induced vasodilation and upregulated KATP channels. The heart rate and blood pressure were not modified. Dandelion leaf and petal phenolic fractions, enriched with l-chicoric acid, are promising plant materials that may exert in vivo beneficial antioxidant effects.